2022
DOI: 10.1021/acssuschemeng.2c05465
|View full text |Cite
|
Sign up to set email alerts
|

Neighboring Site Synergies in Co-Defective Ru–Co Spinel Oxide toward Oxygen Evolution Reaction

Abstract: As is well known that the oxygen evolution reaction (OER) is dominant to determine water splitting, regulating the electronic structure of the electrocatalyst has been demonstrated to be an effective strategy for improving OER activity. Herein, Ru− Co spinel oxides with abundant cobalt vacancies (V Co -RCO) are successfully developed as a highly efficient electrocatalyst for OER. Interestingly, the introduction of Ru can induce the formation of cobalt vacancies, which can modulate the electronic state of V Co … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…The satellite peaks at 720.1 and 730.7 eV further imply the presence of Fe 2+ and Fe 3+ in the electrocatalysts in their prepared state. Results of the XPS analysis showed that Fe substitution caused the generation of cation defects. , Predictably, Fe 2+ and Fe 3+ species were discovered in Ni 0.6 Fe 2.4 O 4 @NC- 1 . This discovery occurred due to the electronic interaction of the Fe and Ni atoms.…”
Section: Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The satellite peaks at 720.1 and 730.7 eV further imply the presence of Fe 2+ and Fe 3+ in the electrocatalysts in their prepared state. Results of the XPS analysis showed that Fe substitution caused the generation of cation defects. , Predictably, Fe 2+ and Fe 3+ species were discovered in Ni 0.6 Fe 2.4 O 4 @NC- 1 . This discovery occurred due to the electronic interaction of the Fe and Ni atoms.…”
Section: Results and Discussionmentioning
confidence: 95%
“…Results of the XPS analysis showed that Fe substitution caused the generation of cation defects. 57 , 58 Predictably, Fe 2+ and Fe 3+ species were discovered in Ni 0.6 Fe 2.4 O 4 @NC- 1 . This discovery occurred due to the electronic interaction of the Fe and Ni atoms.…”
Section: Results and Discussionmentioning
confidence: 97%
“…Liu's group 11 synthesized a new Zn x Ni 1−x Co 2 O 4 /NCNTs composite via the hydrothermal process, in which Zn 2+ substitution could not only afford larger specific surface area and enough structured edge but also produce Zn vacancies (V Zn ), allowing more correct interactions between Co adsorption sites and oxygen-containing intermediates. Pan et al 12 found that Ru doping was made for forming Co vacancies (V Co ), which can regulate the electronic structure of V Co -RCO and generate synergistic effects between Ru and Co, as well as improve the electrocatalytic performance toward OER. As can be seen, larger atom doping is prone to induce cation defects in host materials that could facilitate charge delocalization and reduce overpotentials of electrocatalytic reactions.…”
Section: ■ Introductionmentioning
confidence: 99%